Ectoparasites of the comman vampire bat (Desmodus rotundus) in Costa Rica: parasitism rates and biogeographic trends - Rojas Cartín, Andrés (2008)
Revista Mastozoología Neotropical, 15(2):181-187, Mendoza, 2008